Identification of Soil Contamination using VLF-EM and Resistivity Methods: A Case Study - Inayah, Rahmatun; Santosa, Bagus Jaya; Warnana, Dwa Desa; Syaifuddin, Firman; Rochman, Juan Pandu Gya Nur; Lestari, Wien; Widodo, Amien (IPTEK The Journal for Technology and Science, 2025)
Hazardous waste is a type of waste that has the potential to pollute and harm the environment, human health, and other living beings. Lakardowo is a village suspected of being contaminated by hazardous waste originating from industrial activities. This study utilized the VLF-EM and resistivity methods for subsurface investigation. In addition, groundwater level mapping and soil sampling were conducted around the industrial area for XRF testing. The results of the groundwater mapping indicated that the flow direction leads toward the northeast–south and southwest of the industrial site. The soil samples tested with XRF revealed the presence of heavy metals, which are typically found in hazardous waste and are generally conductive or possess low resistivity values. The quantitative interpretation of VLF-EM data indicated low-resistivity anomalies at several measurement points, which are suspected to be areas where the soil has been contaminated by waste. The resistivity data processing results showed a low-resistivity anomaly (approximately 3 ohm-meters) located to the north (near the industrial site) and spreading toward the southwest along the measurement path. From the combined quantitative interpretation of both methods, it was concluded that the anomalous flow of hazardous waste is moving toward the southeast and penetrating deeper into the subsurface layers, following the dip direction of the rock layers.